IMPLEMENTASI ETIKA BISNIS DI INDONESIA : ADA APA DI CORPORATE GOVERNANCE - Lasmiatun - (DHARMA EKONOMI, 2012)
The weakness of government offices and supportingcommittee in keeping on system exactly, accordances with the function have been fixed. This is more weakening the minority owner, but, on the contrary, it will strengthen the position of majority stock,holdet to exploit. The compang’s resources for it is necessity, eventhongh bring a loss to other people’s necessity(especially the minority stock-holder)The combination between Indonesian capital market’s small relativity with the little of the company ownership propotion (inform) stock, sold to public, make the majority owner in strong position. Especially, by unability control (mechanism of other external) such as marger and acquisition to discipline the company that does not apply the principle of corporate governance exaetly.It’s not found the effort of improvement wholly yet that include the improvement to all component of corporate governance system in supporting to carry outying out this system the application of control mechanism in order to guarantee carrying out this system proporting and continuonsly. Keywords : Corporate Governance, Business Ethic